Assessing the effectiveness of school management committees (SMCs) in improving governance of primary schools in Bangladesh: a case study of selective SMCs at Gouripur Upazila in Mymensingh district - Al Mamun, Mohammad Abdullah (BRAC University, 2014)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2014.